2021
DOI: 10.1016/j.heliyon.2021.e08513
|View full text |Cite
|
Sign up to set email alerts
|

Integration of solar energy into low-cost housing for sustainable development: case study in developing countries

Abstract: The United Nations Development Program reported that two-thirds of the world's population will be living in cities by 2050, which would account for more than 60% of the world's energy consumption. Developing countries experience substantial urbanization and informal settlements compared with other parts of the world. This indicates a paradigm shift in the global energy landscape, which heralds an increase in greenhouse gas emissions. According to Indonesia's National Energy General Plan (PR 22), solar panels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The levelized cost of electricity has dropped significantly in many developing countries, with current levels of USD 0.29/kWh in Uganda and USD 0.27/kWh in Indonesia, for example [68]. The operating lifetime of photovoltaic panels is estimated at 15-20 years in Australia; after which, waste management must be enforced [69].…”
Section: Resultsmentioning
confidence: 99%
“…The levelized cost of electricity has dropped significantly in many developing countries, with current levels of USD 0.29/kWh in Uganda and USD 0.27/kWh in Indonesia, for example [68]. The operating lifetime of photovoltaic panels is estimated at 15-20 years in Australia; after which, waste management must be enforced [69].…”
Section: Resultsmentioning
confidence: 99%
“…Many countries around the world have made different efforts to achieve sustainable development [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], and high-quality development represents active exploration of sustainable development in China. As the Yellow River Basin is an important ecological barrier and economic zone in China, this paper is devoted to the study of HQD in the YRB.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found that energy consumption had a positive and significant impact on economic growth in both groups of countries. Thadani and Go [30] researched the integration of clean energy into low-cost housing developments in sustainable cities in Uganda and Indonesia and found that integrating solar energy into low-cost housing was a viable option. Yang et al [31] focused on the impact of energy consumption on economic growth in East African power pool countries and argued that energy contributed to economic growth in general, while non-renewable energy reduced economic growth in the selected countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Solar energy use in households and the commercial sector is increasing [84,85]. The change from energy consumer to energy producer and consumer (the so-called prosumer) and its impact on the way individuals use energy plays a significant role in the case of energy security [86,87].…”
Section: Solar Energy Systemsmentioning
confidence: 99%